SURVEI NYAMUK AEDES AEGYPTI DAN AEDES ALBOPICTUS DI BANTUL DIY SEPTEMBER-OKTOBER 1992 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
Dengue is still a serious problem in Indonesia and it has been reported from Bantul DIY since 1969. Ovitraps were placed at 35 houses at Dongkelan and 48 houses at Ngeblak, Bantul. The ovitraps were placed in and outside the houses six a week to ditermine the population densities of Ae. aegypti and Ae. albopictus. The results indicated that the population densities ofAedes in Ngeblak were higher than in Dongkelan. The house index of Aedes in Dongkelan and Ngeblak were 65.71% and 91.66% respectively. It has been known that the population densities of Ae. albopictus were higher than Ae. aegypti in both areas. The ovitrap index of Ae. albopictus in and outside the house in Dongkelan were 17.14% and 51.43% respectively, whereas the ovitrap index of Ae. aegypti in and outside the house were 2.86% and 11.43% respectively. Meanwhile the ovitrap index of As. albopictus in and outside the house in Ngeblak were 41.66% and 72.91% respectively, but the ovitrap index of As. aegypti in and outside the house were 18.75% and 14.58% respectively.